P5 Airway responsiveness measurements in asthmatic recruits to emergency services. (16th November 2010) - Wiscombe, S; Jeebun, V; Stenton, SC
Abstract : Asthmatics undertaking emergency service work are thought to be at increased risk of severe bronchoconstriction with sudden exertion or exposure to irritants such as fire smoke, pepper spray or CS gas. The risks are poorly quantified and there are no clear guidelines to assist employers. We investigated the value of airway responsiveness measurements in 40 applicants to the police service who were thought to have asthma at a pre-employment examination. Their mean age was 25 years (SD 6 years); 22 (55%) were male. Only 15 (37%) reported active symptoms (wheeze, breathlessness or cough). Their median FEV1 was 106% of predicted (range 77–125%) and only 3 demonstrated airflow obstruction. Airway responsiveness was measured as PD20 .FEV1 to methacholine using the Newcastle dosimeter technique1 16 (40%) had measurements in the 'definite' asthma range, that is, PD20 .FEV1 <200 μg; 6 in the "equivocal" range PD20 .FEV1 <200–1000 μg; and 18 in the 'normal' range PD20 .FEV1 >1000 μg. There was a clear relationship between pre-employment FEV1 and PD20 within the definite asthma group (F(1, 14) = 9.15; p<0.001) but there were no significant associations between PD20 category and symptoms, medication use or lung function. We conclude that airway responsiveness measurements are practical in this setting and identify more than 50% of asthmatics as probably at low risk of marked bronchoconstriction. Further follow-up of the cohort will be necessary to more precisely determine the risks (Abstract P5 Table 1 ).